Challenges of procurement of works through international open tendering method: a case study on moghbazar-mouchak flyover project - Samad, Kazi Abdus (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.